UPAYA SEKURITISASI PERUBAHAN IKLIM MELALUI TUVALU COASTAL ADAPTATION PROJECT 2012-2024 - Almira Aida Shakira; Firsty Chintya Laksmi Perbawani (Journal Publicuho, 2025)
The research focuses on analysing the Tuvalu government’s efforts to securitise climate change through the Tuvalu Coastal Adaptation Project 2012-2024. The research method employed is descriptive research, which describes phenomena based on occurring facts, utilising secondary data sources through literature studies, including official TCAP policy documents, speeches by Tuvalu officials at UN forums, and statements in mass media. The results of this study found that the securitization efforts by the Tuvalu government through TCAP were successful, as they fulfilled the stages outlined in securitization theory including: (1) securitizing moves through speech acts performed by securitization actors, (2) framing of referent objects that must be protected from existential threats, (3) extraordinary measures taken by securitization actors to ensure the securitization process, and (4) audience acceptanc.